Effective Promotional Strategies: Analyzing the Impact of Flash Sale and Cashback Discounts on Impulsive Buying Behavior in Live Streaming Marketplaces - Adytya; Arya Prakasa; Dede Karunia (Komunitas Dosen Indonesia, 2024)
This research aims to analyze the impact of promotional programs, such as Flash Sales and Cashback Discounts, on impulse buying behavior in the context of a live streaming marketplace, with brand image as a moderating factor. The research method involves an online survey of consumers who actively shop in the live streaming marketplace. Research findings indicate that the Flash Sale program has a significant influence in triggering impulse buying behavior among consumers. Cashback Discount Programs also create a strong motivation for impulse purchases. A strong brand image and good reputation tend to increase the effectiveness of promotional programs. The results of the regression analysis show that the Flash Sale and Cashback Discount programs have a positive and significant effect on impulse buying behavior, and brand image moderates the relationship between promotional programs and impulse buying behavior. The implication of this research is that merchants and e-commerce platforms can utilize Flash Sale and Cashback Discount programs as effective tools to encourage impulse purchases. They must also strengthen their brand image to increase the effectiveness of promotional programs. These implications are relevant in designing smarter promotional strategies in a competitive e-commerce environment. Apart from that, consumers also gain valuable insights to make wiser purchasing decisions in the face of various tempting promotional offers.